2010
DOI: 10.1016/j.ijhydene.2010.03.084
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biohydrogen production from glucose and protein at neutral initial pH

Abstract: GlucoseNeutral initial pH Protein a b s t r a c t Organic wastes are considered as potential substances for economical biohydrogen production, because the carbohydrate and protein are main components. Previous investigations indicate that an optimum hydrogen production appear in acidic conditions to carbohydrates, or in alkali condition to protein. However, in practice, the treatment of these organic wastes by anaerobic fermentation usually carries out at neutral pH condition, in which biohydrogen production i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 27 publications
0
17
1
Order By: Relevance
“…2) was due to the contribution of Celluclast 1.5 L. This is an interesting finding because main components of Celluclast 1.5 L are protein and sorbitol. It has been reported that sorbitol or protein can be fermented to H 2 [31,32]. However, this is the first report that provides experimental evidence of the actual contribution of a commercial enzyme to the H 2 production.…”
Section: Contribution Of Acid and Enzymatic Hydrolysates Constituentsmentioning
confidence: 83%
“…2) was due to the contribution of Celluclast 1.5 L. This is an interesting finding because main components of Celluclast 1.5 L are protein and sorbitol. It has been reported that sorbitol or protein can be fermented to H 2 [31,32]. However, this is the first report that provides experimental evidence of the actual contribution of a commercial enzyme to the H 2 production.…”
Section: Contribution Of Acid and Enzymatic Hydrolysates Constituentsmentioning
confidence: 83%
“…The hydrogen production reached 205.2 mL/g-protein, which was much higher than that reported in the literature2. pH 12 pretreatment induced the unfolding of protein, damaged the protein hydrogen bonding networks, destroyed the disulfide bridges and changed their conformations, which increased the susceptibility of protein to protease and enhanced the hydrolysis of protein9.…”
Section: Discussionmentioning
confidence: 62%
“…Figure 4 displays the rapid decline of HY at an initial cultivation pH of 7.5 (32, 25, 1.4 and 0.05 mL H 2 g -1 glucose at cycle 1, 2, 3 and 4, respectively). It was reported that at cultivation pH 7.7, a batch sole biohydrogen production yielded 140 mL H 2 g -1 glucose at glucose concentration 3 g L -1 [37]. Therefore, the low HY obtained in this study should be correlated to the MB activities, which were increasingly enhanced over cycles (MY was 2, 7, 8 and 37 mL CH 4 g -1 glucose at cycle 1, 2, 3 and 4, respectively).…”
Section: Influence Of Substrate Concentration On Biohythane Productionmentioning
confidence: 60%